Literature Study: Relationship between Inquiry Model and Ability to Understand Mathematical Concept and Students' Learning Independence - Ulya, Syastri; Mulyono, Mulyono; Neem, Chuti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
The application of the inquiry learning model is often related to students' ability to understand mathematical concepts and self regulated in mathematical learning. This is one of the reasons why the relationship between the inquiry learning model and the ability to understand mathematical concepts and self regulated in mathematical learning is interesting to discuss again. Studies regarding the relationship between the inquiry learning model and the ability to understand mathematical concepts and independent mathematical learning have been carried out since the 1960s until now. With the large amount of literature regarding the inquiry learning model on the ability to understand concepts and self regulated in mathematical learning, this article aims to map existing studies on the relationship between the inquiry learning model and the ability to understand concepts and self regulated in mathematical learning. This article is a study that uses a literature study approach. Literature such as books, articles and journals were collected online, namely with the help of the